Visual Sensing of β-Glucosidase From Intestinal Fungus in the Generation of Cytotoxic Icarisid II - Wang, Gang; Yan, Fei; Wang, Yufei; Liu, Yingping; Cui, Jingnan; Yu, Zhenlong; Feng, Lei; James, Tony D.; Wang, Chao; Kong, Ying (Frontiers in Chemistry, 2022)
β-Glucosidase (β-Glc) is an enzyme capable of the selective hydrolysis of the β-glycosidic bond of glycosides and glycans containing glucose. β-Glc expressed by intestinal microbiota has attracted increasing levels of interest, due to their important roles for the metabolism of exogenous substances in the gut. Using the 2-((6-hydroxy-2,3-dihydro-1H-xanthen-4-yl)methylene)malononitrile fluorophore (DXM-OH, λem 636 nm) and the recognition group β-Glucose, an enzymatic activatable turn-on fluorescent probe (DXM-Glc) was developed for the selective and sensitive sensing of β-Glc. In addition, DXM-Glc could be used to sense endogenous β-Glc in living fungal cells. Using DXM-Glc, Pichia terricola M2 was identified as a functional intestinal fungus with β-Glc expression. P. terricola M2 could transform the flavone glycoside Icariin to Icariside Ⅱ efficiently, which confirmed the metabolism of glycosides in the gut mediated by fungi. Furthermore, Icariside Ⅱ could inhibit the proliferation of human endometrial cancer cells (RL 95-2 and ishikawa) significantly, suggesting the metabolic activation of Icariin by intestinal fungi in vivo. Therefore, DXM-Glc as a probe for β-Glc provided a novel technique for the investigation of the metabolism of bioactive substances by intestinal microbiota.